Designing of An Integrated Port Development Planning Model: Application to The Three Main Cameroonian Ports - Jean François Wounba; Christian Alain Bienvenu Ndzie Bitundu; Charles Bwemba; Stephen Kome Fondzenyuy (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
The Chad and the Central African Republic countries threatened to find an alternative to Cameroon's ports because of the low accessibility and inefficiency of these ports. The objective of this study in its relevance is to characterize the current hinterland of Cameroonian maritime ports, to analyze the dynamics of the flow of goods in the port hinterland of Cameroon, and to make recommendations for improving the National Port Master Plan to guarantee the increased development of Cameroonian maritime ports. The Huff model integrated into the Spatial Interaction Model (SIM) is used to geographically delimit the economic hinterland of Cameroon's seaports. The results of the study highlight two key points: (1) the significance of integrating the development of Cameroon’s port hinterland into the national port planning strategy to enhance the growth of the country’s maritime ports. (2) Each port in Cameroon should pay more attention to the expansion of the hinterland. This study introduces methods integrating the SIM approach for practical hinterland exploration with the Bayesian model and mutual information for analyzing hinterland needs. Additionally, it offers recommendations for a seaport development planning model. This article broadens the use of the SIM Bayesian model with mutual information, which can easily be adapted to other scenarios.